Enjoying as a couple to achieve wellness - Silva Cruz, Julio (2019)
The author argues that Transactional Analysis is a personality theory and a psychological intervention system for personal growth and development, which has helped people in their relationships by allowing them to learn to relate in a healthier way. Among the several fundamental elements to manage our lives as a couple, our ability to ENJOY is important.